The Analysis of School Culture In Shaping Students' Character At Islamic High School of Al-Fatah Palembang - Saipul Annur (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This article was conducted to analyze school culture in shaping students' character at MA Al-Fatah. This type of research is qualitative with a descriptive approach. Source of data through interviews, observation, and documentation. Furthermore, data analysis techniques in this study by reducing data, presenting data, and drawing conclusions. Meanwhile, in checking the validity of the data, researchers used four criteria: trust, transferability, dependence, and certainty. Based on the study results that school culture shapes student character, there are two cultural aspects: Academic Culture, which includes a culture of reading, learning culture, and creativity. In contrast, the second culture is Social Culture, 3S culture, and simple living culture. The characters formed through school culture are religious, independent characters, curiosity characters, creative characters, democratic characters, disciplined characters, responsible characters, and social care characters.